Prepositions in Old and Middle English a study of prepositional syntax and the semantics of at, in and on in some Old and Middle English texts - Lundskær-Nielsen, Tom (North-Western European language evolution. Supplement, 1993)
The present book covers various aspects of prepositional syntax between c. 900-1400, including case relations and the range of prepositional complements; it also examines word order, both within the PP and at clause level, and it explores changes in clausal word order. Furthermore, it provides a detailed semantic analysis of the three prepositions at, in and on in selected Old and Middle English texts, which shows to what extent the relative distribution of these prepositions changed during that period and how they gradually acquired new, extended senses. The front cover illustration renders the 895 entry of the Anglo-Saxon Chronicle, Parker Ms., and has been reproduced with the permission of the Master and Fellows of Corpus Christi College, Cambridge